The effectiveness of Audiovisual Education and Spiritual Support Intervention on Anxiety Reduction and Hemodynamic Parameter Stabilization in Pre-Esophago Gastro Duodenoscopy (EGD) Patients: A Pre-Intervention Study - Hidayat, Arif Imam; Mulyaningrat, Wahyudi; Purnawan, Iwan; Awaludin, Sidik; Alivian, Galih Noor; Alfianto, Candra; Siwi, Adiratna Sekar; Walohtae, Fa-is (Journal of Bionursing, 2024)
Background: Pre-procedural anxiety in esophagogastroduodenoscopy (EGD) patients can negatively impact cooperation and physiological stability, increasing procedural risks. This study evaluated the AVOGADO intervention, integrating audiovisual education and spiritual support, to reduce anxiety and stabilize hemodynamic parameters. Methods: A Pre-Intervention Study was conducted on a 45-year-old male with chronic dyspepsia and moderate-to-severe anxiety (HAM-A > 25). The intervention was administered two days prior to the procedure. Anxiety levels were assessed using the Hamilton Anxiety Rating Scale (HAM-A), and hemodynamic parameters, including blood pressure, heart rate, and oxygen saturation, were measured at four time points: three days, two days, one day before, and on the day of the procedure. Result: Anxiety decreased significantly, with HAM-A scores dropping from 26 (moderate-to-severe) to 10 (mild). Hemodynamic parameters improved, with blood pressure reduced from 150/90 mmHg to 130/82 mmHg and heart rate from 98 bpm to 80 bpm. Oxygen saturation remained stable. Conclusion: The AVOGADO intervention effectively reduced anxiety and improved physiological stability in a pre-EGD patient. This simple, holistic approach offers promise for broader application in reducing anxiety in medical procedures. Further research with larger samples is recommended.